Survival characteristics of Salmonella enterica serovar Enteritidis in chicken egg albumen - KANG, H. (Cambridge University Press, 2006)
Salmonella enterica serovar Enteritidis (SE) is a major foodborne pathogen primarily causing human infection through contaminated chicken eggs. To understand how SE survives in chicken egg albumen, we systematically and quantitatively analysed the survival properties of SE in egg albumen and identified factors affecting its survival. Survival assays of SE in egg indicate that egg albumen restricted the growth of SE. A major factor that controlled SE's growth in egg albumen was iron restriction, since egg albumen supplemented with iron allowed SE to grow, and iron acquisition mutants of SE showed decreased survival in egg albumen. In addition, low pH of albumen, high concentrations of bacteria and low incubation temperatures of bacteria with albumen facilitates the survival of SE. Our results suggest that egg albumen uses multiple mechanisms to control SE including iron limitation, surface interaction and possible enzymatic activities.